Fiscal competition on the local level: May commuting be a source of fiscal crises? - Holger Kächelein (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2003)
The paper extends the familiar standard tax competition model for the possibility of cross-border commuting by introducing an additional level of jurisdictions. For separating the impact of landownership and cross-border commuting different schemes of landownership are considered. It will be shown that the possibility of cross-border commuting increases the problem of tax competition since an additional indirect fiscal externality arises via the potential reallocation of labor. The resulting change in the supply of publicly provided goods depends crucially on the considered structure of landownership respectively on the aim of the local policy makers. If the tax burden can be exported via external possession of land, the undersupply of publicly provided goods will be reduced and in the extreme case, an oversupply may arise.
Keywords: H77; H71; J68; 330; Tax Competition; Cross-border Commuting; Fiscal Externalities; Steuerwettbewerb; Gemeindefinanzen; Pendelverkehr; Grundbesitz; Öffentliches Gut; Spillover-Effekt; Theorie